PEMANFAATAN TEPUNG BIJI CEMPEDAK (Artocarpus chempeden) DAN TEPUNG BIJI DURIAN ( Durio zibethinus murr ) DALAM PEMBUATAN BAKSO IKAN - epi susianti; Jumirah .; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT‘Cempedak’ and durian seeds flour are the kind of seeds that are less utilized as a product of the food industry. ‘Cempedak’ and durian seeds flour can be processed into various food product which can give contribute nutrient for schoolchildren. One of the product is fish meatball. This study aims to determine organoleptic and nutritional of modified fish meatball with ‘cempedak’ and durian seed’s flour.This experimental design was completely randomized design with of two factors are ‘cempedak’ and durian seeds flour with composition of 35%:5%, 30%:10% and 25%:15%. Organoleptic test of modified fish meatball was given to thirthy panelist of students of state elementary school 064985 grade VI and then, nutrient analyzed was tested in laboratory of industrial research and standarization Agency Medan. Analyzed was done descriptively.The results showed that organoleptic test of modified fish meatball with ‘cempedak’and durian seeds flour was generally preferred. Of the third fates ,it turns out fish meatball modified comparison 30%: 10% get the highest point and contain protein for the highest.In making fish meatball, it was recommended if the comparison between ‘cempedak’ and durian seeds flour are 30% and 10%. It is need to give information and socialization about ‘cempedak’and durian seeds flour and durian so that can be made, received and used to be additional food of students.Keyword: fish meatball. cempedak seeds flour, durian seeds flour, organoleptic test, elemantary school.